2021
DOI: 10.1111/mice.12712
|View full text |Cite
|
Sign up to set email alerts
|

Vortex‐induced vibration measurement of a long‐span suspension bridge through noncontact sensing strategies

Abstract: Long‐span bridges are susceptible to vortex‐induced vibration (VIV), which affects the serviceability and safety of bridges when the vibration amplitude is too large and lasts for a long time. Traditional contact‐type sensing technologies (i.e., accelerometers and linear variable differential transformer) are inconvenient and dangerous to be installed on long‐span bridges for monitoring VIV events. To address this limitation, this article focuses on the VIV measurement of a long‐span suspension bridge through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The second evaluation method has the advantages of short evaluation cycle and few indicators; however, its disadvantage is that it is relatively intuitive. Static and dynamic load tests can only evaluate the safety status of the bridge at the later stage of the bridge, but it is difficult to find hidden quality problems during the construction process [12][13]. Therefore, it is necessary to propose a method that can not only reflect the construction quality, but also avoid large amount of data and reduce the evaluation difficulty and workload.…”
Section: Health Status Assessment Of Super Span Sbsmentioning
confidence: 99%
“…The second evaluation method has the advantages of short evaluation cycle and few indicators; however, its disadvantage is that it is relatively intuitive. Static and dynamic load tests can only evaluate the safety status of the bridge at the later stage of the bridge, but it is difficult to find hidden quality problems during the construction process [12][13]. Therefore, it is necessary to propose a method that can not only reflect the construction quality, but also avoid large amount of data and reduce the evaluation difficulty and workload.…”
Section: Health Status Assessment Of Super Span Sbsmentioning
confidence: 99%
“…For example, the abnormal reduction of modal frequency is often regarded as an indicator of the loss of structural integrity, and Salawu [13] concluded that 5% reduction of modal frequency was a reliable sign for structural damage. As for damping ratio, it is the key parameter of long-span bridge's wind-resistant capacity, especially for the performance of vortex-induced vibration [14][15][16]. Te reduction of damping ratio may lead to large-amplitu devortex-induced vibration [14].…”
Section: Introductionmentioning
confidence: 99%
“…J. Zhang et al (2021) measured the vortex-induced vibration of a long-span suspension bridge using different noncontact techniques, including the DIC method. Khuc and Catbas (2017) proposed a target-free approach to track scale-invariant feature transform descriptors for displacement measurement, which was validated on an elevated bridge.…”
Section: Introductionmentioning
confidence: 99%